2020
DOI: 10.1177/1088767920924447
|View full text |Cite
|
Sign up to set email alerts
|

From Murder to Imprisonment: Mapping the Flow of Homicide Cases—A Systematic Review

Abstract: This systematic review examined the evidence on factors influencing the flow of homicide, from suspicious death to imprisonment. Bibliographic databases and thesis portals were searched. The total number of hits was 15,986, of which 15,830 were irrelevant, 35 did not include a quantitative sample, 26 did not focus on homicide, 18 did not present flow data, and for seven there was no full text available. The remaining 70 papers were analyzed. With the exception of one, no study presented a complete lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(189 reference statements)
0
6
0
1
Order By: Relevance
“…Several studies have found that the victim's gender has not any significant effect on clearance (Addington, 2006;Puckett and Lundman, 2003), while other scholars have reported a higher likelihood of cases being cleared if they involve either female victims (Lee, 2005;Petersen, 2017;Roberts, 2007) or male victims (Jiao, 2007;Litwin and Xu, 2007;Roberts andLyons, 2009, 2011). The literature indicates that homicides involving child victims are more likely to be cleared (Addington, 2006;Jiao, 2007;Roberts, 2007), while there is more debate on the relationship between elderly victims and homicide clearance (Bänziger and Killias, 2014;Liem et al, 2019Liem et al, , 2020Regoeczi et al, 2020).…”
Section: Perspectives On Homicide Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that the victim's gender has not any significant effect on clearance (Addington, 2006;Puckett and Lundman, 2003), while other scholars have reported a higher likelihood of cases being cleared if they involve either female victims (Lee, 2005;Petersen, 2017;Roberts, 2007) or male victims (Jiao, 2007;Litwin and Xu, 2007;Roberts andLyons, 2009, 2011). The literature indicates that homicides involving child victims are more likely to be cleared (Addington, 2006;Jiao, 2007;Roberts, 2007), while there is more debate on the relationship between elderly victims and homicide clearance (Bänziger and Killias, 2014;Liem et al, 2019Liem et al, , 2020Regoeczi et al, 2020).…”
Section: Perspectives On Homicide Clearancementioning
confidence: 99%
“…As regards the non-discretionary factors, the relevance of the location of the murder has received empirical support: homicides occurring indoors are more likely to be cleared, due to both the possibility of preserving evidence better and the likelihood that an indoor location entails a personal relationship between victim and perpetrator (Addington, 2006;Braga et al, 2019;Litwin, 2004;Litwin and Xu, 2007;Mouzos and Muller, 2001;Regoeczi et al, 2000). Homicides committed with firearms are usually considered to be less likely to be cleared than those committed with other weapons (Liem et al, 2020). This is because firearms involve less contactand hence less evidencebetween the opponents compared to other weapons, such as knives or blunt objects (Braga et al, 2019;Litwin, 2004;Litwin and Xu, 2007;Regoeczi et al, 2020;Roberts, 2007;Roberts and Lyons, 2011;Rydberg and Pizarro, 2014).…”
Section: Perspectives On Homicide Clearancementioning
confidence: 99%
“…Qualquer que seja o país, o fluxo do sistema de justiça criminal, para qualquer crime, terá sempre o formato de funil (Liem, Aarten e Vüllers 2021). O problema se coloca quando a diferença entre a base e o topo é muito elevada, indicando disjunção operacional e comprometendo o possível efeito de dissuasão pela condenação (Liem, Krüsselmann e Eisner 2020). Uma parte da literatura organizacional argumenta que esse formato de funil extremo poderia ser atribuído à existência de objetivos díspares entre os atores institucionais, que estariam mais preocupados com sua sobrevivência do que com a cooperação para o adequado processamento do delito (Crespo 2018).…”
Section: Introductionunclassified
“…There have been previous efforts to compare countries in crime or punishment (e.g., the International Crime Victimization Survey: see, for example, Van Kesteren et al, 2000), but there have been no previous efforts to compare countries on the complete flow diagram from crime to punishment. Liem et al (2020) have completed a systematic review of prior studies of the flow of homicide cases through stages of the criminal justice system. Most studies focused on only one stage.…”
Section: Introductionmentioning
confidence: 99%
“…Liem et al (2020) have completed a systematic review of prior studies of the flow of homicide cases through stages of the criminal justice system. Most studies focused on only one stage.…”
Section: Introductionmentioning
confidence: 99%